An efficient method for determining all the extreme points of function with one variable - Pandiya, Ridwan
An algorithm for determining all the extreme and inflection points to one variable multi-modal global optimization problems is presented. The algorithm is directly suitable for a class of problems of commonly used in solving the global optimization problems. The algorithm is the combination of the filled function's algorithm and Inner Iteration algorithm, called IRH's algorithm, in which Inner Iteration algorithm works at the domain which is usually ignored by filled function's algorithm.